An avant-garde of the mind: Ōe Masanori and psychedelic cinema in the global Sixties. Issue 2 (3rd July 2021) - Noonan, Patrick
ABSTRACT: This essay explores the relationship between cinema and the psychedelic counterculture in the United States and Japan through the life and work of the filmmaker Ōe Masanori. After spending five years producing films within and about the counterculture in the U.S., he returned to Japan in 1969 and quickly became involved in the emerging movements at home. The author argues that Ōe incorporated his understanding of psychedelics into his filmmaking to create forms of cinema that could alter how viewers understood themselves and their relationship to the world in the late 1960s.